2014
DOI: 10.3329/sja.v11i1.18376
|View full text |Cite
|
Sign up to set email alerts
|

Virus elimination in potato through meristem culture followed by thermotherapy

Abstract: Virus elimination in potato through meristem culture followed by thermotherapy and virus indexing was studied. Three levels of thermotherapy, viz.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 6 publications
0
10
0
2
Order By: Relevance
“…However, the fact that the extraction and culture of such a small meristem (0.1 -1 mm) is often problematic and can result in non-desirable somaclonal variations, meristem culture is combined with other techniques such as thermotherapy or chemotherapy to enhance the production of potato virus-free plantlets (Cassells and Long 1982;Ali et al 2014;Aguilar-Camacho et al 2016).…”
Section: Meristem Culture For Potato Virus Eliminationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the fact that the extraction and culture of such a small meristem (0.1 -1 mm) is often problematic and can result in non-desirable somaclonal variations, meristem culture is combined with other techniques such as thermotherapy or chemotherapy to enhance the production of potato virus-free plantlets (Cassells and Long 1982;Ali et al 2014;Aguilar-Camacho et al 2016).…”
Section: Meristem Culture For Potato Virus Eliminationmentioning
confidence: 99%
“…Thermotherapy Combined with Meristem Tissue Culture to Enhance Viral Elimination The study has shown a significant influence of temperature on potato therapy during meristem tissue culture technique on both plantlets survival and the percentage of virus eliminated (Panattoni et al 2013). However, the meristem size, the kind of the virus, the variety of the plant and the duration of the thermotherapy influence the level of heat treatment on the regeneration of meristem derived plantlets and the viral elimination efficiency (Ali et al 2014). So the combined meristem culture with thermotherapy is better than the use of these two techniques alone.…”
Section: Thermotherapy Technique For In Vitro Potato Virus Eliminationmentioning
confidence: 99%
“…However, this is likely to compromise the success of virus elimination since it reduced plantlet survival. The low survival rates for Kinigi and Rwangume even at low thermotherapy exposure periods implied that these cultivars have low tolerance to high temperature (Ali et al, 2013). The higher survival rate of cultivar Victoria after four weeks of heat treatment than the other Table 8.…”
Section: Discussionmentioning
confidence: 94%
“…Torres et al (2000) melaporkan bahwa perlakuan termoterapi atau kultur meristem yang diaplikasikan secara tunggal tidak dapat mengeliminasi virus pada bawang putih, namun ketika kedua perlakuan tersebut dikombinasikan maka eliminasi virus dapat terjadi. Eliminasi virus juga terjadi pada kentang yang diberi kombinasi perlakuan termoterapi dan kultur meristem (Ali et al 2013). …”
Section: Pendahuluanunclassified